Prospective teachers' opinions on the value of PowerPoint presentations in lecturing - Uz, Cigdem; Orhan, Feza; Bilgic, Gulsah (ELSEVIER SCIENCE BV, 2010)
This study examines the prospective teachers' opinions of the PowerPoint presentations used in their courses in order to identify which factors students are pleased with and those which could be improved, and thereby the results of the study is providing an insight into the future use of PowerPoint presentations for academics. Participants were 684 prospective teachers enrolled at four universities in Turkey. Prospective teachers expressed partially positive opinions of the designs of PowerPoint slides and the contribution made to learning by the general use of PP presentations in their courses and furthermore, there was a significant difference between the departments. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: PowerPoint presentations; prospective teachers; lecturing; STUDENTS SELF-EFFICACY; ATTITUDES; CLASSROOM; Education & Educational Research